Ketide Synthase (KS) Domain Prediction and Analysis of Iterative Type II PKS Gene in Marine Sponge-Associated Actinobacteria Producing Biosurfactants and Antimicrobial Agents - Selvin, Joseph; Sathiyanarayanan, Ganesan; Lipton, Anuj N.; Al-Dhabi, Naif Abdullah; Valan Arasu, Mariadhas; Kiran, George S. (Frontiers in Microbiology, 2016)
The important biological macromolecules such as lipopeptide and glycolipid biosurfactant producing marine actinobacteria were analyzed and their potential linkage between type II polyketide synthase (PKS) genes was also explored. A unique feature of type II PKS genes is their high amino acid sequence homology and conserved gene organization. These enzymes mediate the biosynthesis of polyketide natural products with enormous structural complexity and chemical nature by combinatorial use of various domains. Therefore, deciphering the order of amino acid sequence encoded by PKS domains tailored the chemical structure of polyketide analogues still remains a great challenge. The present work deals with an in vitro and in silico analysis of PKS type II genes from five actinobacterial species with known PKS and metabolic products to correlate the domain architecture and structural features shared with known PKS proteins. Our present analysis reveals the unique protein domain organization of iterative type II PKS and KS domain of marine actinobacteria. The findings of this study would have implications in metabolic pathway reconstruction and design of semi-synthetic genomes to achieve rational design of novel natural products.